2013
DOI: 10.1016/j.nlm.2013.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation of object recognition memory requires simultaneous activation of dopamine D1/D5 receptors in the amygdala and medial prefrontal cortex but not in the hippocampus

Abstract: The mesocorticolimbic dopaminergic system includes the ventral tegmental area (VTA) and its projections to the amygdala (AMY), the hippocampus (HIP) and the medial prefrontal cortex (mPFC), among others. Object recognition (OR) long-term memory (LTM) processing requires dopaminergic activity but, although some of the brain regions mentioned above are necessary for OR LTM consolidation, their possible dopamine-mediated interplay remains to be analyzed. Using adult male Wistar rats, we found that posttraining mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 51 publications
7
47
0
Order By: Relevance
“…We have also established that SKF-38393, when given systemically, can reverse the scPCP-induced deficit in NOR in female rats (McLean et al, 2009). This is supported by data reporting that microinfusion of the dopamine D 1 -like receptor antagonist SCH-23390 into the rat mPFC produced a deficit in NOR (Rossato et al, 2013;Clausen et al, 2011).…”
Section: Discussionsupporting
confidence: 71%
“…We have also established that SKF-38393, when given systemically, can reverse the scPCP-induced deficit in NOR in female rats (McLean et al, 2009). This is supported by data reporting that microinfusion of the dopamine D 1 -like receptor antagonist SCH-23390 into the rat mPFC produced a deficit in NOR (Rossato et al, 2013;Clausen et al, 2011).…”
Section: Discussionsupporting
confidence: 71%
“…This suggests that, following the 24 h delay information underlying NOR retrieval was present in the ACgx, which, in line with the findings reviewed above, shows that the NOR information may have been consolidated into the ACgx. As mentioned above, one function of the mPFC is to consolidate NOR memory, and the role of dopamine in the consolidation of long-term memory has recently been investigated by Rossato et al (2013). They infused the D1 receptor antagonist SCH13390 into the mPFC just after the encoding of a NOR task and found that such a manipulation affected consolidation.…”
Section: Discussionmentioning
confidence: 99%
“…Although lesion methods suggest that mPFC is not necessary for object recognition as measured by the standard test variant based on object identity (Ennaceur et al, 1997; Hannesson et al, 2004a; Nelson et al, 2011a), this does not exclude a modulatory role for mPFC. Indeed, evidence that the role of DA D 1 -like receptors in the consolidation of novel object recognition memory (de Lima et al, 2011) is mediated in mPFC has been provided by evidence for DA D 1 regulation of protein synthesis after novel object exposure (Nagai et al, 2007) as well by micro-injection experiments comparing the effects of DA D 1 –like receptor agents with DA D 2 receptor agents in mPFC (Nagai et al, 2007; Rossato et al, 2013). Similarly, we have recently found that novel object recognition is impaired by the DA D 1 agonist SKF81297, both after systemic injections and after microinfusion directly into PL mPFC (Pezze et al, unpublished data).…”
Section: What Where and When: Object Recognition Memorymentioning
confidence: 99%